Cardiac ischemia modulates white adipose tissue in a depot-specific manner - Wang, Luzhou; Zabri, Heba; Gorressen, Simone; Semmler, Dominik; Hundhausen, Christian; Fischer, Jens W.; Bottermann, Katharina (Frontiers in Physiology, 2022)
The incidence of heart failure after myocardial infarction (MI) remains high and the underlying causes are incompletely understood. The crosstalk between heart and adipose tissue and stimulated lipolysis has been identified as potential driver of heart failure. Lipolysis is also activated acutely in response to MI. However, the role in the post-ischemic remodeling process and the contribution of different depots of adipose tissue is unclear. Here, we employ a mouse model of 60 minutes cardiac ischemia and reperfusion (I/R) to monitor morphology, cellular infiltrates and gene expression of visceral and subcutaneous white adipose tissue depots (VAT and SAT) for up to 28 days post ischemia. We found that in SAT but not VAT, adipocyte size gradually decreased over the course of reperfusion and that these changes were associated with upregulation of UCP1 protein, indicating white adipocyte conversion to the so-called ‘brown-in-white’ phenotype. While this phenomenon is generally associated with beneficial metabolic consequences, its role in the context of MI is unknown. We further measured decreased lipogenesis in SAT together with enhanced infiltration of MAC-2+ macrophages. Finally, quantitative PCR analysis revealed transient downregulation of the adipokines adiponectin, leptin and resistin in SAT. While adiponectin and leptin have been shown to be cardioprotective, the role of resistin after MI needs further investigation. Importantly, all significant changes were identified in SAT, while VAT was largely unaffected by MI. We conclude that targeted interference with lipolysis in SAT may be a promising approach to promote cardiac healing after ischemia.